Negotiating the third space in contemporary gamelan: multilaras and rhythmic hybridity in “meeting in the kitchen” by the Kyai Fatahillah Ensemble - Faliq Azka Haikal; Sukanta Sukanta; Abizar Algifari Saiful (Gelar: Jurnal Seni Budaya, 2026)
Research on contemporary gamelan has primarily focused on the musical outcomes of intercultural collaboration, while the artistic negotiation processes underlying hybrid musicality remain insufficiently explored. This study investigates the intercultural collaboration in the Topeng Masquerade project by Ensemble Kyai Fatahillah, focusing on the composition Meeting in The Kitchen, which brought together Indonesian gamelan musicians and the Dutch ensemble Black Pencil. A qualitative case study approach was employed, with data collected through observation, interviews, and documentation analysis. The findings indicate that musical hybridity emerged through negotiations involving laras, tuning systems, rhythmic structures, and patterns of musical interaction. These processes were realized through the application of multilaras, the use of a micro tuning system, the development of call and response patterns between gamelan and Western instruments, changing time signatures, and adjustments between strict tempo practices and the more flexible temporal approach of the Sundanese tradition. The study shows that the collaboration functioned not as cultural fusion but as a dialogic process that preserved the identities of both traditions while generating a hybrid musical form. It concludes that contemporary gamelan can serve as a space for intercultural exchange, fostering new musical identities through collaborative creativity and cultural interaction.